Mitigation of Heat Stress in Broiler Chickens with Heat Shock Protein 70 Gene Expression as its Indicator - Cecep Hidayat; Komarudin .; E Wina (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
Heat stress is an important issue in broiler chicken farms in tropical countries, such as Indonesia. Heat stress is very detrimental to broiler chickens because reducing production performance, health, and causing mortality. In the condition of heat stress, broilers synthesize Heat Shock Protein (HSP) quickly as the body's response to heat stress. HSP70 is the most studied HSP group related to heat stress. The objective of this study was to review the nutritional approach that has been done to mitigate heat stress in broiler chickens with the HSP70 gene expression as its indicator. Based on some studies, nutritional approaches that can be taken are through the management of feed availability, supplementation of vitamin C, vitamin E, plant bioactives, amino acids (taurine and glutamine), probiotics, prebiotics, synbiotics, mannan oligossaccharides (MOS) and minerals (selenium, zinc, manganese, chromium). By these approaches, HSP70 gene expression decreased, indicating that the heat stress level of broiler chicken also reduced. It can be concluded that the nutritional approach can be used as a method for heat stress mitigation in broilers with the HSP70 gene expression indicator.